Effects of Digitization on Audit Methodology - Hegedűs Mihály; Гегедюш М. (ФОП Сабов А. М., 2019)
Abstract. Digitization transforms the environment around us, changes the methodology of tax accounting and auditing activities. The globalization of auditing, tax advisory and accounting facilitate the development of solution centers and creative common thinking. The distorted structure of the SME sectors of individual countries still hinders the construction of unified systems, but the near-term auditing of economic processes is at hand. Continuous audit is an automatic method used to perform audit activities more frequently, such as risk and control assessments. In continuous audit activities, technology plays a key role by helping to automate the identification of exceptions and / or anomalies. Artificial intelligence based modern applications and technologies are excellent for analyzing patterns and reviewing trends. A continuous audit approach allows internal auditors to fully understand critical control points, rules, and exceptions. Due to a faster and more efficient processing of data, auditors can put emphasis on identifying risks, gaining a deeper insight into how the organization works. The gained insight can assist the auditor to focus on high-risk areas.
Вплив цифрових технологій на методологію аудиту
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00007679
Keywords: digitization; audit methodology